2018
DOI: 10.1016/j.jalgebra.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

On the normality of the null-fiber of the moment map for θ - and tori representations

Abstract: Let (G, V ) be a representation with either G a torus or (G, V ) a locally free stable θ-representation. We study the fiber at 0 of the associated moment map, which is a commuting variety in the latter case. We characterize the cases where this fiber is normal. The quotient (i.e. the symplectic reduction) turns out to be a specific orbifold when the representation is polar. In the torus case, this confirms a conjecture stated by C. Lehn, M. Lehn, R. Terpereau and the author in a former article. In the θ-case, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Reducing to the case of (V, G) stable and faithful, we can now demonstrate the following. See also [Bul18,Theorem 2.2], where it was demonstrated independently and simultaneously without the hypothesis of stable that N is normal if and only if it is irreducible. Lemma 5.2.…”
Section: The Case Of G 0 a Torusmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing to the case of (V, G) stable and faithful, we can now demonstrate the following. See also [Bul18,Theorem 2.2], where it was demonstrated independently and simultaneously without the hypothesis of stable that N is normal if and only if it is irreducible. Lemma 5.2.…”
Section: The Case Of G 0 a Torusmentioning
confidence: 99%
“…Note that in the case that (V, K) is unimodular, meaning that all maximal minors of the weight matrix of the action are ±1 or 0, Theorem 1.3 was established in [MN14,Lemma 3.8]. See also [Bul18,Section 3], where it is demonstrated that when G is a torus, the alternate definition given in Equation (2.5) yields complex symplectic quotients that are in general reduced and normal.…”
Section: Introductionmentioning
confidence: 99%